Sense of agency and the role of entertainment in Infinite Jest’s “Living Dead” - Chapman, Ana María (My University, 2018)
This paper attempts to betoken the relevance of emotions in the representation of the body and in the 'reviving' of the self in David Foster Wallace's Infinite Jest. The novel discerns a world where the oversaturation of choices in entertainment has revered a tradition of ennui and addiction as part of the hedonistic search for pleasure. This is of a particular importance to the understanding of the destruction of the self which is consequently framed in the paradoxically position of the 'abject', as one who rejects the self over unreachable pleasure. On the basis of this new definition of entertainment, characters are annularly entrapped in non-agent actions to escape this deadly and stultifying entertainment (through sports, media and/or drugs). Moreover, entertainment invalidates its original meaning as it evokes no true stimuli in the characters in the novel. This significantly shows how individuals are unable to feel any emotion or attachment to the external world. As a consequence, their mind is prosthesized and has lost control over the body which thus suggestively explains why bodies in the novel are described as malleable, machine-like and deformed. This can be enlightened from a neuropsychologist perspective with the claim that emotions play a key role in representing the body. If one feels a detachment from the body and no 'sense of agency', one may state to feel non-existent or dead as no external stimuli evokes emotions in them. Cotard syndrome helps to reveal how the lack of emotions disables a correct representation of the body giving way to the belief that one may be dead, non-existent or deformed. The discussion will lay on how Infinite Jest is a novel, among other things, about the struggle to regain feeling and the lost self from a body perspective and its validating connection to the mind.
Keywords: Foster Wallace, David - Crítica e interpretación; Búsqueda de placer y entretenimiento; Representación de la mente y el cuerpo